EP040/#682 Cervical cancer treatment capacity in Africa: mapping of radiation oncology and gynecologic oncology services. (4th December 2022) - Allanson, Emma; Akinfenwa, Chidinma Anakwenze; Ewongwo, Agnes; Bazzett-Matabele, Lisa; Msadabwe, Susan; Kamfwa, Paul; Shouman, Tarek; Lombe, Dorothy; Rubagumya, Fidel; Rubio, Alfredo Polo; Ntekim, Atara; Vanderpuye, Verna; et al.
Abstract : Objectives: To meet demands for cervical cancer care in Africa, there is a need to understand current access to surgery and radiotherapy. Methods: We collected data on gynecologic and radiation oncology staffing and infrastructure capacities from each African country from February-July 2021 through collaboration by querying partners at the International Atomic Energy Agency, National Cancer Institute, International Gynecologic Cancer Society, and African Organisation for Research and Training in Cancer. Cancer incidence data were obtained from GLOBOCAN. The number of radiation oncologists, therapists, physicists, and gynecologic oncologists were reported. The adequate number of radiation and gynecologic oncologists were both defined as 2 physicians per 1000 cases (assuming a radiotherapy utilization rate of 65% for cervical cancer cases). Results: Six of 54(11%) countries reported an adequate number of gynecologic and radiation oncologists. Seven(13%) had neither. Thirty-one(57%) countries reported external beam radiation availability, 25(46.3%) brachytherapy availability, and 31(57%) gynecologic oncology availability. In 6(11%) countries, general gynecologists perform radical hysterectomies. Where data were reported, there were a median of 2 (range 1–13, IQR 2) physicists and 6 (range 1–40, IQR 7) radiation therapy technicians. The number of countries with training for gynecologic oncology, radiation oncology, medical physics, and radiation therapy was 14(26%), 16(30%), 11(20%), and 17(31%) respectively. Conclusions: This study maps available gynecologic and radiation oncology services for cervical cancer care in Africa. Our results suggest major gaps in infrastructure, human resources, and training. These data serve as a cervical cancer treatment capacity database, which can facilitate multi-national collaborative clinical, implementation and research projects.